Identification of Important Physiological Traits and Moderators That Are Associated with Improved Salt Tolerance in CBL and CIPK Overexpressors through a Meta-Analysis - Ma, Yuanchun; Cheng, Qunkang; Cheng, Zongming; Li, Hui; Chang, Youhong; Lin, Jing (Frontiers in Plant Science, 2017)
The CBL-CIPK pathway is a plant-specific Ca2+ sensor relaying pathway that has been shown to be involved in plant response to salt stress. Over-expression of CBL-CIPK network genes has been reported to increase salt tolerance in many studies. The studies on the overexpression of CBL-CIPK network genes, however, have used various indices to evaluate the effect of these genes on salt tolerance and have indicated a variety of roles for the major CBL-CIPK pathway genes. Therefore, it is of great interest to analyze the various effects resulting from the overexpression CBL-CIPK pathway genes and their relation to salt tolerance. The meta-analysis conducted in the present study investigated how over-expression of CBLs or CIPKs in transgenic plants affects the response to salt stress and identified the increase or decrease that occurs in these experimental variables when foreign CIPK or CBL genes are overexpressed in transgenic plants. The data from the collective studies on over-expression of CIPKs indicated that 6 of the 11 examined parameters (main effects) increased by 22% or more, while 2 of the 6 examined parameters increased by at least 78% in transgenic plants overexpressing CBL genes. In addition to analyzing the impact of overexpression on the main effects, eight different modifying parameters were also analyzed. Results indicated that several moderators impact the extent to which overexpression of CBLs and CIPKs affect the main parameters. The majority of CBLs have been obtained from dicotyledonous plants and most of the CBLs and CIPKs have been expressed in dicotyledonous plants. In comparison to homologous expression, the meta-analysis indicated that heterogeneous expression of CBLs resulted in greater increases in seed germination. The results of the meta-analysis provide information that could be useful in designing research to examine the mechanisms by which CBL-CIPK pathway genes increase salt tolerance in plants.